2013
DOI: 10.5860/crl-301
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Usage of an Electronic Book Collection: Size of the E-book Collection, the Student Population, and the Faculty Population

Abstract: This paper presents the results of a quantitative and systematic investigation exploring online e-book usage at the J.N. Desmarais Library of Laurentian University over a 9-year period. The size of an e-book collection was determined to show evidence of an extremely strong relationship with the level of usage e-books experienced. Of all factors examined during the course of this study, it was the size of the collection that exhibited the strongest association to usage levels and would suggest just how importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 45 publications
1
27
1
1
Order By: Relevance
“…The percentage of all accessed eBooks out of all the collections on offer seems to vary greatly between universities: Waikato patrons have accessed in total about 39% since 2003 (approximately 10% each year), while Sprague and Hunter reported that 16% of Ebrary titles were assessed at least once for the University of Idaho [29], at Australia's Edith Cowan university, 8% of eBooks were browsed and 5% were read (over a three year study period) [1,2], and Swinburne patrons accessed about 48% and created loans for approximately 19% in one month alone (these percentages are calculated from the usage data presented in [22]). Lamothe found strong correlations between the size of eBook collections and the level of eBook usage [20]. We were unable to confirm this for the UoW collections, as the number of eBooks available did not seem to influence the number of eBook sessions.…”
Section: Discussioncontrasting
confidence: 48%
“…The percentage of all accessed eBooks out of all the collections on offer seems to vary greatly between universities: Waikato patrons have accessed in total about 39% since 2003 (approximately 10% each year), while Sprague and Hunter reported that 16% of Ebrary titles were assessed at least once for the University of Idaho [29], at Australia's Edith Cowan university, 8% of eBooks were browsed and 5% were read (over a three year study period) [1,2], and Swinburne patrons accessed about 48% and created loans for approximately 19% in one month alone (these percentages are calculated from the usage data presented in [22]). Lamothe found strong correlations between the size of eBook collections and the level of eBook usage [20]. We were unable to confirm this for the UoW collections, as the number of eBooks available did not seem to influence the number of eBook sessions.…”
Section: Discussioncontrasting
confidence: 48%
“…At the J. N. Desmarais Library, the average cost of an interlibrary loan had been previously calculated to be approximately Can$15.00. 42 Therefore, subscriptions recording a "cost-per-download" greater than the Can$15.00 target for more than three years can be eliminated from the collection.…”
Section: Resultsmentioning
confidence: 99%
“…23 In fact, this practice has been enforced for the past several years and has saved the library a considerable sum of money. 24 For this reason, it is extremely important not to assume the accuracy of usage values without carefully examining the data. The artificial inflation of usage numbers could substantially cost the library if it was believed that an e-resource was beginning to experience an improvement in usage when, in actuality, it was not the case.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2012 Ithaka S+ R US Faculty Survey, users placed the highest need on "access to a wider range of materials in digital format" (Housewright, Schonfeld, & Wulfson, 2013, p. 33). In a detailed study at Laurentian University over a nine-year period, Lamothe (2013) found a relationship between the size of the e-book collection and its use. He wrote that "The level of usage appeared to be directly proportional to the size of the collection."…”
Section: Users Cite Lack Of Contentmentioning
confidence: 99%